The effectiveness of unresisted versus heavy resisted sprints on sprint speed, strength deficit, and force-time measures in youth rugby players - Zabaloy, S.; Pereira, L. A.; Gálvez-González, J.; Tondelli, E.; Alcaraz, P. E.; Freitas, T. T.; Loturco, I. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Although both unresisted sprint training (UST) and resisted sprint training (RST) are widely used in rugby and other team sports, evidence comparing their specific effects on neuromuscular adaptations and strength-related measures is still limited. This study aimed to analyze the effects of two sprint training programs—UST and RST, using 50% of body mass—on secondary outcome measures and force-time characteristics obtained from the squat one-repetition maximum (squat 1RM-strength), associated strength deficits (SDef from 40% to 90% 1RM), isometric squat, Nordic hamstring exercise (NHE), and jump performance in youth rugby players.